Heart Rate Variability and Muscle Strength in Young Adults with Sedentary Behaviour - Juliana, Norsham; Zolkafi, Mohd Azrul Anuar; Azmani, Sahar; Abu, Izuddin Fahmy; Mon Sarip, Noor Aein; Abu Yazit, Noor Anisah; Mohd Fahmi Teng, Nur Islami; Das, Srijit (IIUM Medical Journal Malaysia, 2021)
Introduction: Sedentary behaviour or physical inactivity has been relatively prevalent among young adults globally. Multiple studies pointed out that Malaysia has been listed as one of the Asian countries with high prevalence of inactivity. Objective: This study aimed to examine the heart rate variability (HRV) and muscle strength among young adults in order to identify the early impact of this behaviour on their physiological and physical health. Method: This cross-sectional study involved 185 healthy male adults aged 18-25 years old. Participants’ height and body compositions were measured and their level of physical activities were obtained using Short Questionnaire to Assess Health (SQuASH). Those with less than 150 minutes per week of physical activity engagement were classified as sedentary. Their HRV was analysed as a determinant for early physiological change that was influenced by the sedentary behaviour. Muscle strength of upper and lower body was assessed via handheld dynamometer to identify the physical fitness associated to the behaviour. Results: Among the participants that volunteered in this study, approximately 44% were classified as sedentary. Analyses revealed that those with sedentary behaviour had lower variability of their HRV and lower muscle strength as compared to those who engaged with at least 150 minutes per week of physical activities. Conclusion: The highlighted evidence of the difference on parameters of HRV and muscle strength with this behaviour suggested that these parameters were suitable parameters to be utilised in determining subclinical improvement on health with any intervention to curb sedentary behaviour.